Laser-assisted charge transfer in He2++H collisions - Anis, Fatima; Roudnev, V.; Cabrera-Trujillo, R.; Esry, B. D. (My University, 2006)
The time-dependent Schrödinger equation is solved numerically to investigate laser-assisted charge transfer in He2++H+nhν collisions at 1keV in the semiclassical impact parameter approach. Laser polarizations parallel and perpendicular to the projectile trajectory are studied. For both polarizations even a moderately intense laser (I0=3.5×1012W/cm2) significantly increases the reaction probability. In addition, we find that the relative collision-laser phase has little influence on the charge transfer. We focus on parameters more favorable to experiment.